A gestão de parques tecnológicos e o desenvolvimento regional : um estudo de caso na região nordeste do Brasil - Feitoza, Regina Aparecida Alves (2016)
This study investigates what are the technological park management models and regional development. To that end, we present elements found in the literature that characterize technology parks, show several parks management models as well as the role of stakeholders and what incentives and promotions arising from the parks that influence regional development, which later we were confronted with case studies of objects of this research parks. They were analyzed what each researched park management models, as defined Kang (2004) and management strategies that affect the development process of the Parks lease area, as well as how the actors involved in the parks contribute to the development of the region, is that financial, social and/or intellectual. As for the methodological aspects, the approach to research is classified as descriptive and as the method itself as qualitative. Regarding the time dimension, the study is cross-sectional. As for the strategy, was adopted multiple case study where four technology parks was analyzed in operation in northeastern Brazil, according to a study conducted by ANPROTEC (2013). For data collection was used the techniques of documentary research and in-depth interview. As a result, it was revealed that three of the four surveyed parks have the same management model, with only slight differences in their structures, are non-profit organizations established to vitalize the development of regional economy. Only one of the parks has a very different structure, however, present the same goals of others. In this way all the parks have next strategies for boosting the local economy, such as the attraction of medium and large companies to the region, the deployment of an entrepreneurial culture and the creation of jobs and income. As well as the relationship with the various stakeholders to come up with common actions to surveyed parks. All, it points out that the management of a park, influences the development of the region, therefore, are from their strategies aspects that promote local development are outlined.